Physical fitness from a health perspective: Conceptual foundations and promotion mechanisms in contemporary society - Chenini, Abdellatif; Faggous, Lahcen; Merzougui, Oussama (Journal of Ecohumanism, 2025)
Through a systematic review and analysis of prior research published since 2010, this study sought to examine the notion of physical fitness from a health perspective as well as the strategies for fostering it. The study analyzed and discussed the results of scientific research in this area using a review methodology. According to the analysis, the idea of healthy physical fitness has changed over time to encompass five key elements: flexibility, neuromuscular fitness, muscular fitness (strength and endurance), body composition, and cardiorespiratory fitness. In addition, the study identified a number of interrelated mechanisms for promoting physical fitness, which were divided into three categories: technology-based (smart applications and wearable devices), societal (the role of media, the workplace, and government policies), and individual (intrinsic motivation, lack of goals, and health awareness). The findings also emphasized the primary obstacles to promoting physical fitness, with a particular emphasis on sedentary lifestyles and the psychological and social costs they entail. According to the study’s findings, encouraging physical fitness necessitates an integrated approach that connects societal, technological, and individual factors. This highlights the pressing need to direct future health policies toward all-encompassing programs that take these complexities into account.